Determinação e degradação eletroquímica do estrogênio natural estrona usando anodos de diamante dopado com boro - Brocenschi, Ricardo Francisco (2013)
Different electrochemical techniques were used to characterize the boron-doped diamond (BDD) electrode and to determine estrone. After parameters optimization, the detection limits obtained using differential pulse voltammetry (0.27 μmol L 1) and square-wave voltammetry (0.096 μmol L 1) with a cathodically pretreated BDD electrode were comparable to values reported in the literature. An even smaller value was obtained when amperometric detection was used with a flow injection system FIA-EC (0.050 μmol L 1), because there is a reduction of capacitive current interferences when a fixed potential is applied, as the continuous flow rate (surface cleaning and mass transport effect). In all cases, the BDD electrode presented a stable response (inter- and intra-day repeatabilities) and different matrices did not have significant influence on the detection of estrone. Consequently, the investigated techniques are promising for this purpose, with excellent accuracy and precision. In the electrochemical degradation of estrone studies in a flow reactor a rapid decay of estrone concentration was attained, due to the high oxidation power of the BDD electrode. This decay is dependent on the studied parameters (current density, flow rate, and pH); best results were attained at pH 3. Intermediate products formed during electrolyses of estrone at different pH (3, 7, and 10) were investigated by LC-MS/MS; thus, inedited (partial) degradation pathways were proposed, aiming at understanding the influence of pH on the generation of intermediates. Finally, electrochemical degradation of estrone at pH 7 using the BDD electrode was compared with the one attained with a β‒PbO2 electrode, also with an inedited mechanistic study.